2007
DOI: 10.1088/0957-4484/18/11/115717
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction and Raman scattering studies on large-area array and nanobranched structure of 1D MoO2nanorods

Abstract: One-dimensional (1D) MoO2 nanorods in the form of a large-area array and nanobranched structure were prepared by hot-filament metal–oxide vapour deposition at low and high pressures in atmospheric argon flows respectively. The x-ray diffraction (XRD) patterns of both as-synthesized samples show that the 1D MoO2 nanorods are monoclinic crystals in space group P 21/c. The Raman spectrum of the large-area array of 1D MoO2 nanorods appears to be the same as that of a two-dimensional (2D) MoO2 thin film. The Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 37 publications
11
79
0
Order By: Relevance
“…The XRD and Raman spectra ( Fig. 3c and d) confirm that the resulting nanotubular structures are of orthorhombic MoO 3 phase [23]. Earlier studies using tungsten filament also resulted in both tungsten oxide nanowires and nanotubes in the same experiments [15].…”
Section: Description Of the Hot-wire Assisted Nanowire Synthesis Methodssupporting
confidence: 66%
“…The XRD and Raman spectra ( Fig. 3c and d) confirm that the resulting nanotubular structures are of orthorhombic MoO 3 phase [23]. Earlier studies using tungsten filament also resulted in both tungsten oxide nanowires and nanotubes in the same experiments [15].…”
Section: Description Of the Hot-wire Assisted Nanowire Synthesis Methodssupporting
confidence: 66%
“…Raman spectroscopy measurements indicated that the surface of the S-0-0 coating consisted primarily of the MoO 2 phase whereas data taken in its wear track revealed the presence of the a-MoO 3 phase in addition to MoO 2 . Both phases are the most stable oxides of molybdenum where the oxidation states of Mo are tetravalent and hexavalent for MoO 2 and a-MoO 3 , respectively [42]. However, the Raman spectra for Mo 2 N/MoS 2 /Ag nanocomposite coatings indicated the presence of Ag 2 Mo 4 O 13 silver molybdate phase [19] in addition to a-MoO 3 and MoO 2 .…”
Section: °C Testsmentioning
confidence: 98%
“…The D-band corresponds to disordered carbon, whereas the G-band represents the in-plane bond-stretching motion of the pairs of sp 2 carbon atoms (E 2g phonons). [ [29,30] Microscopic structures of MoO 2 @C-Gas hybrids were characterized by electron microscopes. Fig.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%